Study on the performance and mechanism of aging asphalt with organic–inorganic composite rejuvenator - Benan Shu; Guodong Zeng; Leifeng Li; Maocong Zhu; Yunlong Ma (AIP Advances)
This work studied the performance effect and regeneration mechanism of the organic–inorganic composite rejuvenator (COWRGO) composed of waste cooking oil, waste rubber powder, and modified graphene oxide on aged asphalt. The findings demonstrate that the rejuvenator retained its storage stability for one year following its restoration. The rutting factor of COWRGO regenerated asphalt was 43% higher than that of the base asphalt at 64 °C. A reduction in stiffness of 33% was observed, accompanied by an increase in m of 15% at a temperature of −18 °C. The unrecoverable creep compliance was decreased by 58% under shear stresses of 0.3 kPa. The optimal content of modified graphene oxide was identified as 0.1%. In this instance, the residual penetration rate was increased by 29%, and the viscosity aging index was reduced by 23%. The fatigue life of the regenerated asphalt was increased by 22%, reaching a total of 1610 cycles. Regenerated mechanism tests revealed that the COWRGO process resulted in a reduction in the molecular weight of aged asphalt, with an 11% decrease in the relative content of large molecules and an increase in medium and small molecules. The activation of waste rubber powder results in the formation of a loose and porous structure, accompanied by an increase in oxygen content of 3.79%. The decreased peak intensity of –CH2– and increased peak intensity of C–O and –OH mean that the aged asphalt molecular chains are effectively broken down, and the unsaturated and oxygen-containing functional groups are significantly increased.